BEHAVIORAL FINANCE AND ITS IMPACT ON CORPORATE FINANCIAL DECISION MAKING - Alfiana Alfiana; Muhammad Azizi; Andi Primafira Bumandava Eka; I Kadek Wira Dharma Prayana; Srifatmawati Ahmad (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Behavioral finance has become an important field of study that bridges psychology and financial decision-making. This article examines the impact of behavioral finance on corporate financial decision-making through a literature review of studies published since 2020. Key behavioral biases—such as overconfidence, loss aversion, and herd behavior—are analyzed for their influence on corporate strategies, including investment decisions, risk management, and capital budgeting. The findings reveal that these biases often lead to suboptimal financial outcomes, such as overly aggressive or overly conservative investment decisions, as well as an inability to manage risks effectively. This underscores the importance of integrating behavioral insights into corporate governance to mitigate the negative effects of these biases. Practical recommendations are provided, such as improving financial literacy, managerial training, and implementing structured decision-making processes. This study contributes to the growing body of literature by synthesizing recent research and offering actionable insights to enhance corporate performance. By understanding and addressing behavioral biases, organizations can make more rational and effective financial decisions in the face of complex economic challenges